Secondary School Students' Readiness for Autonomous English Learning in West Java - Hanifah Nur' Aini; Anita Dewi Ekawati (JPG: Jurnal Pendidikan Guru, 2024)
Autonomous English learning grows student’s ability to take responsibility for their own English learning process. The level of student’s awareness of learning English independently is still uneven. Some students’ are ready to learn English independently, whereas others still depend too much on the role of an EFL teacher. Regarding this condition, the study was interested in discovering the secondary school students’ readiness for autonomous English learning in West Java. This study used a quantitative research methodology and a survey as the research tool. Secondary school students from various West Javan schools participated in this study. The data was gathered through a questionnaire. The findings revealed that the students believed that teachers are in charge of almost every aspect of the English learning process. Further, most students are ready enough to learn English independently. Also, students’ have a plan for learning English based on their willingness. The result indicated the teacher had to start applying learning autonomy and encouraging student autonomy in English learning.